Foundation of Progressive Movement in Punjab and its Thematic Influence on Punjabi Novel: A Research Study - Rouf, Abdul (sourcecoder, 2024)
Many of the world’s major languages are replete with short stories, tales, and narratives. Before the emergence of the novel, storytelling and folk tales were common traditions, often revolving around romantic stories or folk tales. Over time, as humanity progressed through different stages of development, this storytelling tradition gradually stories evolved into the form of novels, transitioning from oral storytelling and folk tales into a more structured narrative format. The novel became a unique genre of prose literature, through which writers explicitly express the events and facts that occur in society. A movement is a force or shift that breaks the stagnation of a particular process, but the nature of its expression varies across different spheres of life. The progressive movement has also had a significant influence on this literary expression. This expression and impact of the Progressive Movement too had a diverse influence across different aspects of life. Like other world literatures, Punjabi literature has been deeply influenced by the progressive movement. Punjabi literature, Particularly the Punjabi novel exhibits numerous impacts of this movement, with its artistic, intellectual and thematic aspects being noteworthy. This article aims to explore the foundation of progressive movement in Punjab and the thematic influence of the Progressive Movement on Punjabi novels.